What happened to Turkish currency markets after the 2008 financial crisis? Presenting a model of AMOS path diagram - (:unkn) unknown (My University, 2012)
This paper aims to search the relations of two different types of variable sets with the financial crises of Turkey. The main macroeconomic variables - first set of variables -have been examined via the global financial crisis of 2008 and the research shows how these indicators have affected the financial crisis. Second set of the variables are main money market indicators that are considered to be affected by the financial crises. Based on the quarterly weighted average interest rates on deposits, real effective exchange rates and international reserve data between the years 2006 and 2011, financial pressure index on Turkish economy has been computed to proxy for the country specific financial crises. The relation between relative macroeconomic variables and financial crisis of 2008 and the behavior of currency related variables in Turkey are determined using quarterly data between 2006 and 2011. The relations between the indicators have been analyzed by using AMOS (Analysis of Moment Structures), a structural equation modeling (SEM) software where the model is presented in an intuitive path diagram to show hypothesized relationships among variables. © EuroJournals Publishing, Inc. 2012.
Keywords: AMOS (Analysis of moment structures); Financial crises; Money market variables; Turkish financial markets